2008
DOI: 10.1002/cncr.23813
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide rechallenge in recurrent malignant glioma by using a continuous temozolomide schedule

Abstract: BACKGROUND. Despite advances in first‐line therapy, there are few data on treatment of glioblastoma multiforme (GBM) at recurrence. Temozolomide (TMZ) is well tolerated and may have activity despite prior TMZ exposure if novel dose schedules are used. METHODS. The authors reviewed their experience with a continuous TMZ schedule (50 mg/m2 daily), given at progression after conventional 5‐day TMZ. Patients were reported in 3 groups: 1) GBM after progression on conventional TMZ; 2) GBM at first recurrence after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 17 publications
(27 reference statements)
1
89
0
4
Order By: Relevance
“…It was developed as a DNA alkylating agent that directly damages tumor cells (5)(6)(7). TMZ is stable in acidic conditions, but breaks down to 5-(3-methyltriazen-1-yl)imidazole-4-carboxamide (MTIC) and forms methyldiazonium ions in alkaline conditions, such as the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was developed as a DNA alkylating agent that directly damages tumor cells (5)(6)(7). TMZ is stable in acidic conditions, but breaks down to 5-(3-methyltriazen-1-yl)imidazole-4-carboxamide (MTIC) and forms methyldiazonium ions in alkaline conditions, such as the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Temozolomide (TMZ) is the most widely used chemotherapy for GBM and is orally administered (5). TMZ is a small-molecule DNA alkylating agent that easily penetrates the blood-brain barrier and elicits DNA methylation to effect tumor cell death (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53] In vivo evidence for the direct involvement of MGMT in the response of glioblastoma to alkylating agents has been provided by The Cancer Genome Atlas. 54 The value of temozolomide in the setting of recurrent glioblastoma, including its relationship with MGMT promoter methylation status, must now to be determined in patients who have already been exposed to temozolomide in the first-line setting, 55,56 as is being pursued in the DIRECTOR trial (http://clinicaltrials.gov, NCT00941460).…”
Section: The Role Of Mgmt In Glioma Subtypes Glioblastomamentioning
confidence: 99%
“…Although TMZ does not have US Food and Drug Administration (FDA) approval for use in recurrent GBM, smaller studies of dose-dense regimens have shown some efficacy with its use for this indication [14][15][16]. The theory behind dose-dense TMZ regimens is that they more effectively deplete MGMT, so that the affected DNA cannot be repaired, allowing the tumor cells to be more susceptible to the antitumor activity of the alkylating agent [11,17].…”
Section: Dosing Regimensmentioning
confidence: 99%